(untitled) (Journal of EAHIL, 2017)
A literature review was conducted to identify articles on leadership in the library and information profession since 2011. Articles identified were examined in terms of demand for leadership skills and supply of professional development opportunities. The leadership profile of skills and competencies is diverse: flexibility is the key within the rapidly changing landscape of the profession. Available training and development opportunities range from formal training programmes to low-cost approaches that can be easily implemented by individuals or within organisations.